Critical functions for STAT5 tetramers in the maturation and survival of natural killer cells - Jian-Xin Lin (Nature Portfolio, 2017)
IL-15 signals through STAT5 to modulate natural killer (NK) cell maturation, function and homeostasis, but the specific contributions of STAT5 dimers and tetramers are still unclear. Here the authors show that, while STAT5 dimers are sufficient for NK development, STAT5 tetramers are essential for NK homoeostasis by modulating apoptosis.